Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan PT Federal International Finance (FIFGROUP) Cabang Samarinda - Ahmad Fahreza (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
Good and poor person's performance can be influenced by many factors, among others is the granting of reward and punishment. Reward and punishment are two forms of methods to motivate, encourage and encourage employees to do good and improve their performance. This research aims to determine the influence between Reward and Punishment PT Federal International Finance (FIFGROUP) Samarinda branch both partially and simultaneously to the employee's performance. The population of this research is all employees of PT Federal International Finance (FIFGROUP) branch of Samarinda. Data collection in this study using questionnaires. Data analysis tools used validity test, reliability test, classical assumption test, multiple linear regression test, coefficient of determination test, F test and T test. From this research concluded that effect of apartial reward of the employee’s performance amounted to 48.5%, of the results Tcount>Ttable (3,919>1,993), and a partial punishment influence on the employee’s performance of 60.9%, of the result Tcount>Ttable (3,748>1,993), and simultaneously there was an influence between reward and punishment to performance by 50.2%, from the result of Fcount>Ftable (38,529>3,123). The results showed that the partial and simultaneous reward and punishment have significant effect on the employee's performance. PT Federal International Finance (FIFGROUP) should provide appropriate reward and punishment to improve employee performance.